GIFT-AI: “I’m scared that the AI feedback is too much!”—preservice (English) teachers’ feedback strategies and their use of GenAI for feedback - Fredriksson, Anna-Lena (Frontiers in Education, 2025)
This paper presents a learning activity intended to increase preservice (or inservice) teachers’ skills in giving feedback to students by comparing and discussing teacher feedback and generative AI (GenAI)-powered feedback. In current times, feedback is seen as a dialogue, a two-way relation striving to engage learners in the feedback process, and the way feedback is phrased is considered essential for students to interpret and act on. Teachers often struggle with questions of how much feedback to give, what to give feedback on, and how to phrase it. For inexperienced teachers, the feedback process is particularly challenging, making practice essential. The recent fast-paced development of GenAI tools is transforming the field of L2 writing and feedback practice. Although a multitude of automated writing evaluation systems offer both instant and extensive feedback to students, it is far from evident how they can or should be used in the language classroom. For novice and preservice teachers, who are often cautious in giving corrective feedback, GenAI tools present additional challenges. The activity outlined in this paper provides these teachers with guided practice in giving feedback and enables them to compare their feedback against GenAI-powered feedback on authentic learner text. Classroom discussion on responsible use of AI feedback to promote learning is central to this process. Although designed for the (English) language classroom, the exercise can easily be adapted to other disciplines.